A prokineticin-like protein responds to immune challenges in the gastropod pest Pomacea canaliculata. (July 2017) - Accorsi, Alice; Benatti, Stefania; Ross, Eric; Nasi, Milena; Malagoli, Davide
Abstract: The golden apple snail Pomacea canaliculata is an invasive pest originating from South America. It has already been found in Asia, the southern United States and more recently in the EU. Aiming to target the immune system of the snail as a way to control its spreading, we have developed organ-specific transcriptomes and looked for molecules controlling replication and differentiation of snail hemocytes. The prokineticin domain-containing protein Astakine 1 is the only cytokine known thus far capable of regulating invertebrate hematopoiesis, and we analyzed the transcriptomes looking for molecules containing a prokineticin domain. We have identified a prokineticin-like protein (PlP), that we called Pc-plp and we analyzed by real-time PCR (qPCR) its expression. In control snails, highest levels of Pc-plp were detected in the digestive gland, the ampulla ( i.e., a hemocyte reservoir) and the pericardial fluid ( i.e., the hematopoietic district). We tested Pc-plp expression after triggering hematopoiesis via multiple hemolymph withdrawals, or during bacterial challenge through LPS injection. In both cases a reduction of Pc-plp mRNA was observed. The multiple hemolymph withdrawals caused a significant decrease of Pc-plp mRNA in pericardial fluid and circulating hemocytes, while the LPS injection promoted the Pc-plp mRNA drop in anterior kidney, mantle and gills, organs that may act as immune barrier in molluscs. Our data indicate an important role for prokineticin domain-containing proteins as immunomodulators also in gastropods and their dynamic expression may serve as a biosensor to gauge the effectiveness of immunological interventions aimed at curtailing the spreading of the gastropod pest P. canaliculata. Highlights: A prokineticin-like protein ( Pc- PlP) is expressed in several organs of Pomacea canaliculata . Pc-plp is maximally expressed in digestive gland, ampulla and hematopoietic tissue. Pc-plp expression is specifically altered in different organs by diverse immune challenges. Pc-plp mRNA appears to be post-transcriptionally regulated as astakines in crustaceans. Pc-plp may represent a biosensor to evaluate the immune system status after different challenges.